Expected Roles and Functions of the School Management Committee: An Investigation for Effective Functioning - Sehrawat, Meena; Roy, M. M. (South Asian Journal of Social Sciences and Humanities, 2021)
Community has always been essential in giving significant education to children and members of a community have taken the liability of educating their children. Attempts have been made to improve participation of the community in schools by creating committees like Village Education Committees and School Management Committees. But questions always remain, how far are the communities practically engaged with schools? Significant provisions concerning constitution and functions of SMCs are given in sections of the RTE Act, 2009. With the above in background the present study was taken up with two broad objectives: first, to study the expected roles and functions of the school management committee; and, second to find out and suggest measures for smooth functioning of school management committee. A descriptive survey method was used to collect the data from 390 school management committee members using Questionnaire. The data were quantitatively analyzed using percentage. Responses obtained through questionnaire were converted in to frequencies followed by their conversion in to percentage. Findings revealed that members involved themselves in the monitoring of the admission, attendance and participation of child but didn’t ensure some of the key expected roles and functions and in order to function smoothly, SMCs should be elected through proper election process as per RTE act and SMC members should be oriented by the principals and other authorities. This study can be useful for all the stakeholders involved at the planning, implementing and evaluating the functioning of the School management Committee or community participation in schools. This study focusses on expected roles and functions of school management committee as per the RTE Act and finds new that if members do not function as per the RTE Act, municipal school which is the miniature of the society is going to suffer in providing the quality education as well as implementation of true decentralization.